Training in the current arrangements for free movement of CARICOM nationals : trainer manual (CARICAD BridgetownBB, 2012)
Provides step-by-step instructions on the agreed procedures for free movement of CARICOM nationals to be used by immigration officers throughout CARICOM, at the borders and in offices. It is based on the provisions of the Revised Treaty of Chaguaramas, the decisions of the Conference of Heads of Government and the agreed procedures adopted by the Council for Trade and Economic Development (COTED).
Keywords: TRAINING